Chocorvo Arma Archaeology, Huaytara, Huancavelica - Van Dalen Luna, Pieter Dennis (2015)
We present the characteristics of three pre-Hispanic archaeological sites identified in the town of Chocorvo Arma, Huancavelica. Cultural affiliation sites correspond to the nation late Chukurpu, sociopolitical entity that developed in the scope of the present province of Huaytará immediately before the annexation of these territories to Tawantinsuyu.